Combaterea corupţiei – condiţie necesară pentru dezvoltarea socială şi economică a Republicii Moldova şi integrarea ei în Uniunea Europeană - Mocanu, Victor; Mîndru, Valeriu (Calitatea Vieții, 2009)
The article was written as a result of a sociological study on corruption in the Republic of Moldova and its impact on society. Study data were compared with similar research carried out previously in Moldova. Based on the results of scientific research, a number of recommendations, was developed which are critical both for specialists working in the field of fighting corruption, and for researchers in the field of social and human sciences.